Feminism in the Twentieth Century Afro- American Novel: A Special Reference to Alice Walker's The Color Purple (1982) - BERREHOUMA, ZEKKOUR, Zineb Souhaila (University of Eloued جامعة الوادي, 2018)
"اللون الأرجواني"كتبت من طرف احدى نساء الأدب الأفرو أمريكي"أليس وولكر". تتناول روايةقصة امرأة في مجتمع يمتاز بالهيمنة في بدايات القرن العشرين, وتحاول البطلة مقاومة الظلم و الهيمنة المفروضين عليها بمساعدة شخصيات نسوية أخرى. لذلك تسعى بطلة الرواية لتحقيق المعرفة الذاتية والروحية للسيطرة على حياتها الشخصية بنفسها و عدم تدخل الآخرين بها. تهدف الدراسة للتحري عن الأسباب التي أدت الى تأسيس الحركة النسوية إضافة الى دراسة الهدف من الكتابات النسائية الأفرو أمريكية. لذلك أجريت هذه الدراسة لتسليط الضوء على الكاتبات السود و دراسة كيفية قيامهم بتجسيد ابداعهم من خلال الروايات التي بدورها وجدت لتوحيد اصواتهم و فرض انفسهم في مجتمعهم عن طريق شخصيات رواياتهم الخيالة. و لهذا فإن النظرية النسوية طبقت من أجل اكتشاف مختلف المواضيع التي تناولتها الرواية. في النهاية, كشفت الدراسة بان الكاتبة 'أليس ولكر' قامت باستعمال منهجية الرسائل من أجل تضمين القارئ ضمن شخصياتها من أجل تسهيل عملية فهمه لمعاناة النساء السود وكيف يتم قمعهم و اضطهادهم في مجتمعهم في ذلك الوقت. The Color Purple is written by one of the most prominent figure of Afro-American women's writers, "Alice Walker", the novel pursues the life of a colored woman in the ordinarily dominant society of the early twentieth century. The main character of the novel tries to challenge the circumstances of her society by the support of other female characters that help her to resist the oppression and dominance that she experienced in her life in order to discover herself and find her own voice to control her life by her own. The study aims to investigate the reasons behind the emergence of the Feminist Movement as well as examining black feminist goal behind their writings. Thus, the study is conducted to spot the light on black women writers and how they apply their creativeness through novels which they used to find their own voice and to represent themselves in their society through presenting the different situations of oppression they experienced with their society through their fictional characters. Hence, the feminist theory is used to explore the major themes of the novel. Eventually, the study reveals that the author of the novel "Alice Walker" uses the epistolary form to involve the reader within her characters to allow him to understand well how black women are oppressed in their society during that time.
Keywords: قمع, هيمنة, الحركة النسوية, منهجية الرسائل; Dominance, Epistolary Form, Feminist Movement, Oppression